Recherche et identification de bactéries pathogènes au sein d'une écloserie nurserie d'huître creuse, Crassostrea gigas, en relation avec la mortalité estivale du naissain - Waechter, Magali (Université de La Rochelle, 2001)
Summer mortality has been observed on oyster spat Crassostrea gigas since 1991 on french coasts. In our study, we deseribed symptoms observed during the mortality, especially adductor muscle weakness and we isolated strains on Zobell medium and TCBS from moribund spat. Strains isolated during a high mortality (60 %) were selected by experimental pathology on spat. Inoculation by bath led us to select a pathogenic strain (TNEMF6) for oyster spat. Phenotypic identification, phylogenetic study on 16S rDNA and quantitative DNA/DNA hybridisation showed that this strain belongs to Vibrio splendidus biovar II. Phenotyping and ribotyping with strains isolated during the study showed that only TNNIII7 and TNMB5 are similar to the pathogenic strain TNEMF6. Quantitative DNA/DNA hybridisation showed that only TNNIII7 belongs to the same specie than TNEMF6. Difficulty to isolate these strains of Vibrio splendidus II suggested that they may be located out of the tissues. A pathogenic effect with proteolytie exotoxins is suspected related to the weakness of the adductor muscle observed on moribund oyster spat. Then we project to search for detection probes specific to Vibrio splendidus biovar II and pathogenic strains of this specie Depuis 1991 , des épisodes de mortalité estivale de naissain d'huître creuse, Crassostrea gigas, sont observés sur le littoral français. Au cours de notre étude, nous avons décrit des signes observés en relation avec la mortalité, notamment une faiblesse du muscle adducteur et nous avons isolé des souches bactériennes sur milieux de Zobell et TCBS à partir de naissain moribond. Certaines souches isolées au cours d'un épisode particulièrement fort (60 %) sur notre site d' étude ont fait l'objet d'une sélection en pathologie expérimentale. L' inoculation effectuée par balnéation a permis de sélectionner une souche bactérienne (TNEMF6) pathogène pour le naissain d'huître creuse. L' identification phénotypique, l'étude phylogénétique à partir des 16S rDNA et l'hybridation quantitative ADN/ADN ...